A Comparative Study of the Adsorption Efficiency of the Newly Synthetic Nano Iron Oxide and Commercial Activated Charcoal Towards the Removal of the Nickel(II) Ions. Issue 4 (2012) - Kanthimathi, G.; Kotteeswaran, P.; Thillai Arasu, P.; Govindaraj, P.; Kottaisamy, M.
Abstract : The synthetic nano iron oxide (SNIO) was synthesized by acid base hydrolysis and characterized by the XRD, SEM and EDAX techniques. Batch adsorption experiments were carried out to study the sorption behaviour of SNIO and commercial activated charcoal (CAC) towards Ni(II) ions as a function of initial concentration of the adsorbate, adsorbent dosage, contact time and pH. The adsorption for Ni(II) is found to be better in acidic pH for both SNIO and CAC. The equilibrium adsorption isotherm data have been tested by applying both Freundlich and Langmuir isotherm models. The Separation factor R was found to be between 0 and 1 for both the adsorbent, it clearly indicates the feasibility of adsorption.